Analisis Sektor/Sub Sektor Unggulan di Kabupaten Bungo - Gafur Gafur; Muhammad Safri; Siti Hodijah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2016)
Abstract. This study aimed to analyze the leading sectors in Bungo. The method used is Location Quotient (LQ), Dynamic Location Quotient (DLQ), specialization index, Growth Ratio Model (MRP). Based on analysis of LQ and DLQ, there are only two basis sectors at present and in the future, namely the construction sector and trade, hotels and restaurants. Based on the analysis of Specialization Index, in Bungo Regency has a concentration of the economy in the agricultural sector and the manufacturing sector. Based on MRP analysis also showed that prominent sector growth at the level of Bungo and Jambi Province, namely electricity, gas and water supply; the building sector; and trade, hotels and restaurants. Keywords : Location Quotient (LQ), Dinamic Location Quotient (DLQ), Specialization Index, Growth Ratio Model   Abstrak. Penelitian ini bertujuan untuk menganalisis sektor unggulan di Kabupaten Bungo. Metode yang digunakan adalah analisis Location Quotient (LQ), Dinamic Location Quotient (DLQ), indeks spesialisasi, Model Rasio Pertumbuhan (MRP). Berdasarkan analisis LQ dan DLQ,  hanya ada 2 sektor yang menjadi sektor basis pada saat ini dan pada masa yang akan datang yaitu sektor bangunan dan sektor perdagangan, hotel dan restoran. Berdasarkan analisis Indeks Spesialisasi, di Kabupaten Bungo telah terjadi konsentrasi ekonomi pada sektor pertanian dan sektor industri pengolahan. Berdasarkan analisis MRP juga dapat diketahui bahwa sektor yang menonjol pertumbuhannya pada tingkat Kabupaten Bungo dan Provinsi Jambi yaitu sektor listrik, gas dan air bersih; sektor bangunan; serta sektor perdagangan, hotel dan restoran. Kata Kunci : Location Quotient (LQ), Dinamic Location Quotient (DLQ), indeks spesialisasi, Model Rasio Pertumbuhan